Management of the development of border regions as a tourist destination (Journal of Economic Research & Business Administration, 2021)
The subject of this article is about the development of tourist activities in the region. The increase inthe material well-being of the local population leads to an increase in the social level. The subject of thisarticle is the development of tourist activities in the Lankaran economic region, which is a border region.The object of the research is the tourist activity of the border region.The research method is a comparative analysis of tourism in the economic region of Azerbaijan.The main attention is paid to the mechanism of management of the development of the border region.The development of the border region as a tourist destination is the main goal in the proposed work. Toachieve the goal, it is proposed to create a special economic zone for tourist destinations in the indicatedterritory. The leadership for the implementation of the adopted Development Program is transferred tothe Regional Tourism Council. The implementation of the adopted regional development program isassociated with the development of tourist clusters, the attraction of domestic and foreign investors, entrepreneursof related industries, and joint activities in the region. The development of the region locatedat the state border presupposes close cooperation of the regions on both sides of the state border, the transformation of the region into an international transport hub. The results of this work can be applied tothe management of regional tourism activities. The article concludes that a clear administrative phasedimplementation of the Program as a result will lead to an increase in the volume of the region’s domesticproduct, an improvement in the quality of services offered and, as a result, an increase in the materialwell-being of the local population, and the recognition of the region in the international tourism market.Promotion of the region as a single tourist product will speed up the process of recognizing this territoryas a tourist destination.Key words: cross-border region, special economic zone for tourism, tourism cluster, single tourismproduct.